Analisis Pemahaman Zakat terhadap Membayar Zakat di Baznas pada Kalangan Civitas Akademik Sekolah Tinggi Agama Islam Yogyakarta - Ayu, Navirta (Fakultas Ekonomi dan Bisnis Islam IIQ An Nur Yogyakarta, 2023)
Zakat may very well be an alternative to government programs as a source of funds to alleviate poverty. The benefits of zakat are not only a form of capital, zakat can overcome the problem of accumulation of assets in certain circles in social life, so that the income gap between groups in society can be minimized. The management of zakat by Baznas is regulated based on Law no. 23 of 2011. This study aims to determine the effect of understanding zakat, faith, religious understanding, and organizational skills on compliance with paying zakat at Baznas among the academic at the STAI Yogyakarta. The research method used is a quantitative approach. The independent variable in this research is the understanding of zakat, faith, understanding of religion and organizational skills in managing zakat and the dependent variable is the level of compliance with paying zakat. The results of the analysis show that the understanding of zakat, faith, understanding of religion and organizational skills have a significant effect on zakat paying compliance among the academic at the STAI Yogyakarta.